Developing a mini automated greenhouse for indoor planting - Lee, SimonYan Sheng (2022)
The current studies of automated greenhouse systems are mainly focused on industrial scale projects. Hence, the operating conditions for irrigation system, ventilation system and artificial light source are require extensive studies in order to adapt the automation technology into the mini-greenhouse. The scope of this project is to develop an automated mini-greenhouse for indoor farming, which has the ability to control the greenhouse’s environment such as temperature, air humidity, and soil moisture. Furthermore, the study also determinesthe effectiveness of artificial light (LED) on plant growth compared to natural sunlight. The utilisation of LED light in automated planting was able to promote the growth of Allium fistulosum (green onion), in terms of plant height and number of leaves, as well as natural sunlight applied in the traditional setup. The internal environment, in terms of temperature and air humidity of the automated greenhouse were well controlled compared with the traditional planting system, which depends on the weather. Furthermore, the study also found that a sprinkler system is a suitable irrigation system for small-scale planting and closely arranged plants such as green onions. The power consumption of the sprinkler system is lower for each irrigation circle (0.056 Wh compared to 0.167 Wh) and a shorter time is required per irrigation compared to a drip system (20 seconds compared to 30 minutes). Lastly, plant growth and development such as integrity, colour as well as the presence of pests are also included in the study. Based on the study, the specimens in automated mini-greenhouse show better results in terms of leaves’ integrity, colour (greenish and bright) as well as the pests’ control compared to traditional planting. Generally, the application of an automated minigreenhouse, which has the ability to protect the plants from pests as well as weather conditions, provide better plant growth and development compared to traditional planting.